Hidden Meanings: Researching Student-Teacher Intercultural Competency Using Multicultural Children's Literature - Matea Butković; Ester Vidović (Društvene i Humanističke Studije, 2023)
In modern society, future teachers need to be able to recognize the potential offered by multicultural children's literature in promoting intercultural values in children as well as to feel confident in their ability to choose authentic teaching materials. Three picture books (The Rabbits' Wedding, Morris Micklewhite, and the Tangerine Dress and And Tango Makes Three) and one illustrated story (The Story of Little Black Sambo) were selected for research of students’ intercultural competence. The general research aim was to research the intercultural competence of Teacher Education students using authentic works of multicultural children's literature, whereby the specific aims sought to explore: a) students’ attitudes about the appropriateness of the selected topics for lower elementary school teaching; b) students’ ability to recognize whether the text and illustrations of the selected picture books/illustrated story promote intercultural values (e.g., acceptance of diversity, equality, empathy); c) whether students are trained to recognize the controversial content in the selected picture books/illustrated story, d) student’ self-assessed readiness to address the selected topics in their future teaching; e) student’ self-assessed difficulty in recognizing the representation of intercultural values in the content of the selected picture books/illustrated story. The sample of participants included fifty-six fourth-year Teacher Education students (40 students from the University of Rijeka and 16 students from the University of Pula) during two consecutive academic years (2020/2021 and 2011/2022). The participants filled out a questionnaire that examined the concordance between the content of the selected titles and the promotion of intercultural values, the existence of controversial topics, and the appropriateness of addressing the selected topics in lower elementary school teaching as well as the students’ self-assessed abilities to implement the topics of the selected works in their future teaching and the difficulty of recognizing intercultural values in the selected works were explored. The majority of students recognized the controversial nature of the three selected picture books – the implicit advocacy of the rights and equality of marginalized groups (same-sex adoption, depiction of transgender people, marriage of people of different skin color). Almost two-thirds of the participants encountered difficulties in assessing the presence of intercultural values in the selected literary works.